Absorption Capacity using Waste Paper Sludge as an Alternative Adsorbent for Treatment of Landfill Leachate. Issue 1 (December 2020) - Yahaya, Izat; Daud, Zawawi; Fauzi, Basirah
Abstract: Adsorption treatment process is one of the techniques that has been employed to treat discharge or effluent from domestic wastewater (DWW), raw water and also landfill leachate. The potential of waste paper sludge (WPS) and activated carbon (AC) as an absorbent has been investigated to obtain the optimum mixing ratio in removing two working parameters such as ammonia nitrogen (NH3 -N) and COD. Both WPS and AC were mixed together in different ratio. The absorption batch study is regarding the preparation of 5g composite adsorbent, 200 mL of raw leachate sample at pH 8.64, with a rotational agitation speed of 200 rpm for 300 minutes at room temperature. The result shows, the optimum ratio obtained for composite mixture absorbent is (1:3) and the concentration capacity achieved for the ratio was 870 mg/L and 496 mg/L for NH3 -N and COD, respectively. The Langmuir and Freundlich isotherm studies for NH3 -N and COD presented the adsorption mechanism that occurs on the composite adsorbent is physical and chemical reaction by obtaining the R 2 in both model (< 1) respectively during the experiment.